2013
DOI: 10.1007/s12687-013-0168-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards genetic testing in those affected with Parkinson’s disease

Abstract: Advances in genetic tests provide valuable information for clinicians and patients around risks and inheritance of Parkinson's Disease (PD); however, questions arise whether those affected or at risk of PD will want genetic testing, particularly given that there are no preventive or diseasemodifying therapies currently available. This study sought to determine knowledge and attitudes toward genetic testing for those affected with PD. A cross-sectional study was undertaken using a standardized questionnaire wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Study revealed very positive attitudes toward universal tumor screening, consistent with literature that report on patients' attitudes toward universal tumor screening specifically [38,44] and genetic screening tests generally [33,[46][47][48]. An overwhelming majority of the participants were willing to have their tumors screened if a universal screening program were available to them, consistent with existing literature [44,46,[48][49][50]. Given this study measured hypothetical willingness to take part in tumor screening, it is not known if the positive attitudes observed in this study would translate into actual tumor screening uptake [51].…”
Section: Discussionsupporting
confidence: 89%
“…Study revealed very positive attitudes toward universal tumor screening, consistent with literature that report on patients' attitudes toward universal tumor screening specifically [38,44] and genetic screening tests generally [33,[46][47][48]. An overwhelming majority of the participants were willing to have their tumors screened if a universal screening program were available to them, consistent with existing literature [44,46,[48][49][50]. Given this study measured hypothetical willingness to take part in tumor screening, it is not known if the positive attitudes observed in this study would translate into actual tumor screening uptake [51].…”
Section: Discussionsupporting
confidence: 89%
“…Such research may offer some insight as to how others perceive genetic counseling as these are related services, and in our anecdotal experience, often not easily distinguished by those outside the profession. A majority of these studies involve persons at-risk for a specific disease (e.g., Klitzman 2010;Meiser et al 2008;Scuffham et al 2014; Thomas et al 2007). Population-based studies examining attitudes toward genetic testing/screening are less numerous.…”
Section: Perceptions and Attitudes About Genetic Testingmentioning
confidence: 99%
“…Indeed, surveys of patients and caregivers reveal a high level of interest in genetic testing for PD. 18,19 Exome sequencing (ES) has accelerated the discovery of PD genetic risk factors [20][21][22] and is ideally suited to identify single nucleotide variants (SNVs) in genetically heterogeneous diseases. In one study of adult patients referred for diverse clinical indications, ES had a diagnostic yield of 10% in individuals over 30 years of age.…”
Section: Introductionmentioning
confidence: 99%